Modulation of EndMT by Hydrogen Sulfide in the Prevention of Cardiovascular Fibrosis - Lara Testai; Vincenzo Brancaleone; Lorenzo Flori; Rosangela Montanaro; Vincenzo Calderone (Antioxidants, 2021)
Endothelial mesenchymal transition (EndMT) has been described as a fundamental process during embryogenesis; however, it can occur also in adult age, underlying pathological events, including fibrosis. Indeed, during EndMT, the endothelial cells lose their specific markers, such as vascular endothelial cadherin (VE-cadherin), and acquire a mesenchymal phenotype, expressing specific products, such as α-smooth muscle actin (α-SMA) and type I collagen; moreover, the integrity of the endothelium is disrupted, and cells show a migratory, invasive and proliferative phenotype. Several stimuli can trigger this transition, but transforming growth factor (TGF-β1) is considered the most relevant. EndMT can proceed in a canonical smad-dependent or non-canonical smad-independent manner and ultimately regulate gene expression of pro-fibrotic machinery. These events lead to endothelial dysfunction and atherosclerosis at the vascular level as well as myocardial hypertrophy and fibrosis. Indeed, EndMT is the mechanism which promotes the progression of cardiovascular disorders following hypertension, diabetes, heart failure and also ageing. In this scenario, hydrogen sulfide (H2S) has been widely described for its preventive properties, but its role in EndMT is poorly investigated. This review is focused on the evaluation of the putative role of H2S in the EndMT process.